GAMBARAN KONSEP DIRI PADA ORANG TUA DENGAN ANAK USIA SEKOLAH DASAR DI DESA GUMIWANG KECAMATAN WURYANTORO - Nurtanti, Susana (Jurnal AKPER GSH, 2018)
The background of this study is to determine the level of self-concept possessed by parents and parents. Of the 200 neglected children studied in Surabaya, it is known that only 3.5% of respondents admitted to having never been mistreated by their parents or their families. Almost all neglected children admit to having been the object of violence in the family (96.5%), and even 61% of them admit to being treated harshly. Of the 200 abandoned children, 70% admitted that they were often victims of beatings at home, 66% admitted that they were abused. The purpose of this study was to determine the level of self-concept that parents have to support the psychological development of elementary school age children. The design of this research is descriptive, the number of samples is 50 respondents with purposive sampling technique. The results showed that the results of statistical data processing showed that the frequency distribution of self-concept with good scores was 39 (78.0%), while the frequency distribution of self-concept with bad scores was 11 (22.0%). The results of research in Gumiwang Village showed that most parents have good self-concept.